Evaluating fixed-film nitrification systems in autotrophic mode: enhanced biomass retention does not improve bioreactor performance during alkalinity induced stress. Issue 2 (15th December 2021) - Ronan, Evan; Kroukamp, Otini; Liss, Steven N.; Wolfaardt, Gideon M.
Abstract : Fixed-film bioreactors with different biomass loads operated in parallel. Similar ammonia removal rates indicated a lack of biomass-concentration dependent mechanisms to overcome alkalinity induced stress. Abstract : Use of fixed-film systems has shown promise towards improving the process stability of biological nitrogen removal (BNR). It allows for biofilm formation, which can offer enhanced resilience to environmental stressors such as variable ammonia loading or low temperatures. However, the extent to which this phenomenon extends to periods of alkalinity induced stress has not been fully explored and was therefore the purpose of this study. The nitrification performance of three continuous stirred-tank reactors (CSTRs) was investigated to determine the effect of enhanced biomass retention on nitrification performance under variable alkalinity conditions, including extended periods when the buffer content of the medium was stoichiometrically limited. The bioreactors were established with different surface area to volume ratios using BioCord™, which had the effect of enabling significantly different biomass retention characteristics, as confirmed by time-resolved quantification of total protein in the attached and suspended phase. Chemical analyses indicated that enhanced biomass retention offered the capacity to achieve higher ammonia removal rates during batch mode operation with continuous aeration and excess alkalinity, however, it did not provide any advantage toward alleviating the effects of alkalinity limitation ( e.g. low pH of 4.5–5.5) when the bioreactors were operated in continuous-flow mode. Acidification of the bulk liquid coincided with incomplete ammonia removal, and similar ammonia removal rates were consistently detected in each of the bioreactors regardless of their total biomass concentrations. Under the lowest alkalinity conditions, the ammonia removal efficiency and removal rate in each bioreactor was approximately 24% and 0.006 mmol L −1 h −1, respectively. Thus, higher retention of nitrifying biomass in fixed-film systems did not appear to provide any biomass concentration-dependent mechanisms to overcome the stress brought on by alkalinity depletion. This study provided important insight into the stable operation of BNR systems and demonstrated a potential limitation with respect to the perceived benefits of enhanced biomass retention within fixed-film systems.